Field-programmable silicon temporal cloak - Feng Zhou (Nature Portfolio, 2019)
Temporal cloaks, which hide a temporal event within a signal, have been previously limited to very short and periodic event cloaking. Here the authors report a temporal cloak with a programmable-length cloaking window using a silicon microring and optical frequency comb.